Ang II acutely stimulates Na, K‐pump in cells from proximal tubules by increasing its phosphorylation at S938 via a PI3K/AKT pathway. Issue 21 (14th November 2022) - Hanna, Fadia S.; Alkhouri, Samaa; Rajagopalan, Carthic; Ji, Kyungmin; Mattingly, Raymond R.; Yingst, Douglas R.
Abstract: Angiotensin II (Ang II)‐dependent stimulation of the AT1 receptor in proximal tubules increases sodium reabsorption and blood pressure. Reabsorption is driven by the Na, K‐pump that is acutely stimulated by Ang II, which requires phosphorylation of serine‐938 (S938). This site is present in humans and only known to phosphorylated by PKA. Yet, activation of AT1 decreases cAMP required to activate PKA and inhibiting PKA does not block Ang II‐dependent phosphorylation of S938. We tested the hypothesis that Ang II‐dependent activation is mediated via increased phosphorylation at S938 through a PI3K/AKT‐dependent pathway. Experiments were conducted using opossum kidney cells, a proximal tubule cell line, stably co‐expressing the AT1 receptor and either the wild‐type (α‐1.wild‐type) or an alanine substituted (α‐1.S938A) form of rat kidney Na, K‐pump. A 5‐min exposure to 10 pM Ang II significantly activated Na, K‐pump activity (56%) measured as short‐circuit current across polarized α‐1.wild‐type cells. Wortmannin, at a concentration that selectively inhibits PI3K, blocked that Ang II‐dependent activation. Ang II did not stimulate Na, K‐pump activity in α‐1.S938A cells. Ang II at 10 and 100 pM increased phosphorylation at S938 in α‐1.wild‐type cells measured in whole cell lysates. The increase was inhibited by wortmannin plus H‐89, an inhibitor of PKA, not by either alone. Ang II activated AKT inhibited by wortmannin, not H‐89. These data support our hypothesis and show that Ang II‐dependent phosphorylation at S938 stimulates Na, K‐pump activity and transcellular sodium transport. Abstract : Angiotensin II‐dependent stimulation of the rat kidney Na, K‐pump in proximal tubules is mediated at least in part via an increase in the phosphorylation of the Na, K‐pump at S938 through a PI3K/AKT(PKB)‐dependent pathway, not by PKA. S938 is a conserved site of phosphorylation on all four isoforms of the human Na, K‐pump and was thought to be exclusively phosphorylated by PKA. The Na, K‐pump is the active transport mechanism that drives sodium reabsorption in the proximal tubule, which increases blood pressure. Therefore, the identification of this signaling pathway to phosphorylate the Na, K‐pump at S938 in response to angiotensin II is potentially relevant to human physiology.